2014
DOI: 10.1371/journal.pone.0091426
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture-Like Stimulation at the Baihui (GV20) and Dazhui (GV14) Acupoints Protects Rats against Subacute-Phase Cerebral Ischemia-Reperfusion Injuries by Reducing S100B-Mediated Neurotoxicity

Abstract: ObjectivesThe purpose of this study was to evaluate the effects of electroacupuncture-like stimulation at the Baihui (GV20) and Dazhui (GV14) acupoints (EA at acupoints) during the subacute phase of cerebral ischemia-reperfusion (I/R) injury and to establish the neuroprotective mechanisms involved in the modulation of the S100B-mediated signaling pathway.MethodsThe experimental rats were subjected to middle cerebral artery occlusion (MCAo) for 15 min followed by 1 d or 7 d of reperfusion. EA at acupoints was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…MCAO induces a significant increase in NF-kB, which in turn mediates the transcription of mRNA and an increase in TNF-α expression up to 7 days after the ischemic event [72]. iNOS synthesizes large amounts of NO (nitric oxide).…”
Section: Discussionmentioning
confidence: 99%
“…MCAO induces a significant increase in NF-kB, which in turn mediates the transcription of mRNA and an increase in TNF-α expression up to 7 days after the ischemic event [72]. iNOS synthesizes large amounts of NO (nitric oxide).…”
Section: Discussionmentioning
confidence: 99%
“…Similar changes have been shown to be associated with cell transformation and cancer development [3,12,13]. In addition, the absence of pin1 affects embryonic fibroblasts, leading to rapid genomic instability and the so-called immortality due to inactivation of p53 and further to aggressive transformation and carcinogenesis [16].…”
Section: Introductionmentioning
confidence: 63%
“…They found that TNF-α expression was lower in the EA group than in the model and sham-operated groups [7]. In a study by Cheng et al, acupuncture at the Baihui (GV 20) and Dazhui (GV14) acupoints significantly downregulated the expression of TNF-α, GFAP, S100B, and nuclear factor-kB in the ischemic cortical penumbra [8]. Jiang et al selected Shuigou (GV 26) and Fengfu (DU16) for acupuncture treatment of traumatic spinal cord injury and found that EA had anti-oxidative, anti-inflammatory, and anti-apoptotic effects as indicated by reduced expression of inflammatory cytokines, including TNF- α [9].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the beneficial effects of EA on stroke [68], spinal cord injury [9], arthritis [10], and sciatica [11]. Recently, we have demonstrated that application of EA 60 min post-TBI has neuroprotective effects on neuronal cells.…”
Section: Introductionmentioning
confidence: 94%